Fieldwork among Women in Nepal: A Female Researcher Revisits Her Experience - Mishra, Mira (Dhaulagiri Journal of Sociology and Anthropology, 2018)
In this paper, I argue, based on in-depth interviews with 75 rural women from 25 households in Nepal nearly eight years ago, that a reflection on fieldwork helps a researcher to critically review and critically appreciate one’s own work and to identify challenges that can be helpful not only to the researcher but also other researchers. I describe three distinct stages of my fieldwork. The first one relates to the image I held regarding rural women’s life and society as well as the information generation techniques I thought I ought to utilize before I actually went to the field. The second stage relates to the learning I gained during the fieldwork regarding rural women’s life and society and the manner in which I actually went about generating information. The third stage relates to how I now reflect back on the lives women lead in rural areas as well as the techniques I utilized to generate information. In the concluding section, I attempt to identify the gains I made while I traversed through the three different stages of research.